The Philippines’ distinct path under Duterte: Closer ties with China - Amalia, Sri Reski (Universitas Islam Malang, 2024)
President Duterte's administration is showing a different approach to Philippine economic and political policies which previously leaned more towards the West, through concept formation Dutertismo And Dutertenomics. Dutertismo refers to Duterte's authoritarian, populist leadership style and focus on solving domestic issues such as drugs and terrorism, often with an approach that is at odds with the human rights values upheld by the United States. Meanwhile, Dutertenomics is a massive infrastructure development policy designed to increase the Philippines' economic competitiveness, with a focus on projects that support the Philippines' integration in China's Belt and Road Initiative (BRI). The research method used is an explanatory approach with the aim of explaining the cause-and-effect relationship between Duterte's policies and the shift in Philippine alliances, as well as their impact on the country's economic policy and foreign relations. The research results show that the mismatch between the human rights values upheld by the United States and Duterte's policies encourages the Philippines to seek a solution by strengthening relations with China, which is considered more pragmatic in supporting Duterte's agenda. Dutertenomics designed as a response to China's BRI, with a focus on infrastructure development as a way to improve connectivity and boost the Philippines' economic growth. This research also notes challenges in implementing this policy, such as dependence on foreign loans and domestic political uncertainty, which may affect the sustainability of this agenda.